Inkjet printing of single-walled carbon nanotube/RuO2 nanowire supercapacitors on cloth fabrics and flexible substrates - Chen, Pochiang; Chen, Haitian; Qiu, Jing; Zhou, Chongwu (Nano research, 2010)
Single-walled carbon nanotube (SWNT) thin film electrodes have been printed on flexible substrates and cloth fabrics by using SWNT inks and an off-the-shelf inkjet printer, with features of controlled pattern geometry (0.4–6 cm 2 ), location, controllable thickness (20–200 nm), and tunable electrical conductivity. The as-printed SWNT films were then sandwiched together with a piece of printable polymer electrolyte to form flexible and wearable supercapacitors, which displayed good capacitive behavior even after 1,000 charge/discharge cycles. Furthermore, a simple and efficient route to produce ruthenium oxide (RuO 2 ) nanowire/SWNT hybrid films has been developed, and it was found that the knee frequency of the hybrid thin film electrodes can reach 1,500 Hz, which is much higher than the knee frequency of the bare SWNT electrodes (˜158 Hz). In addition, with the integration of RuO 2 nanowires, the performance of the printed SWNT supercapacitor was significantly improved in terms of its specific capacitance of 138 F/g, power density of 96 kW/kg, and energy density of 18.8 Wh/kg. The results indicate the potential of printable energy storage devices and their significant promise for application in wearable energy storage devices.